2013
DOI: 10.1111/pops.12056
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Flanker Task to Political Psychology: A Research Note

Abstract: One of the two stated objectives of the new “Research Note” section of Political Psychology is to present short reports that highlight novel methodological approaches. Toward that end, we call readers' attention to the “flanker task,” a research protocol widely employed in the study of the cognitive processes involved with detection, recognition, and distraction. The flanker task has increasingly been modified to study social traits, and we believe it has untapped value in the area of political psychology. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 42 publications
(49 reference statements)
3
24
0
Order By: Relevance
“…Consistent with the results of McLean et al. (), effects of political orientation were observed only in the context of being presented with angry (i.e., threatening) faces, so that conflict‐related N2 amplitudes on these trials were larger among children of liberals (and moderates) than conservatives. This pattern of results conceptually replicates, in children, an effect of political orientation on neurocognitive functioning that was documented in a study of adults by Amodio et al.…”
Section: The Nature Of Left‐right Differences In Political Orientationsupporting
confidence: 87%
“…Consistent with the results of McLean et al. (), effects of political orientation were observed only in the context of being presented with angry (i.e., threatening) faces, so that conflict‐related N2 amplitudes on these trials were larger among children of liberals (and moderates) than conservatives. This pattern of results conceptually replicates, in children, an effect of political orientation on neurocognitive functioning that was documented in a study of adults by Amodio et al.…”
Section: The Nature Of Left‐right Differences In Political Orientationsupporting
confidence: 87%
“…Thus, it is possible that threat-related contexts may amplify neurocognitive differences between liberals and conservatives, whereas pleasant or neutral contexts would not. Consistent with this notion, McLean and colleagues (2013) found that conservatives, but not liberals, displayed enhanced sensitivity to angry targets, measured by reaction times indexing greater attentional focusing. In the present study, we varied the emotional context of conflict monitoring by displaying an angry face (threat-relevant) or a comparison face (happy or neutral) prior to each trial of a flanker task.…”
Section: Effects Of Parental Ideology On Neural Sensitivity To Cognitmentioning
confidence: 55%
“…Ideological differences in conflict processing might also be moderated by the emotional context in which cognitive processes operate (McLean et al, 2013). The past decade has seen an explosion of research demonstrating that individual differences, such as enhanced sensitivity to negative and threat-related stimuli, moderate the impact of emotional factors on cognition (e.g., Dennis & Chen, 2007; Hofmann, Ellard, & Siegle, 2012; Ohrmann et al, 2007).…”
Section: Effects Of Parental Ideology On Neural Sensitivity To Cognitmentioning
confidence: 99%
See 2 more Smart Citations